2021
DOI: 10.1111/bjh.17978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of donor characteristics on T cell‐replete haploidentical stem cell transplantation over the last 10 years at a single institution

Abstract: One of the most complex issues with haploidentical stem cell transplantation (haplo-SCT) is donor selection, given that multiple haploidentical donors are often available for a given recipient. To develop evidence-based guidance for donor selection in the setting of anti-thymocyte globulinbased haplo-SCT, we performed a prospective cohort study of 512 patients with haematological malignancies who had haplo-SCT to determine which donor variables were most important in favouring transplant outcomes. Increasing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
0
13
1
Order By: Relevance
“…2,15,25 Our team found the 10-year cumulative incidence of NRM was 14% (95% CI, 11-18) in patients with hematologic malignancies who underwent haplo-SCT. 3 The low NRM at 10 years post-transplant in our studies may be due to median age of our patients was 30 (9-64) years, which was much younger than most of the previous large studies. Meanwhile, the optimization of transplant procedures and the improvement of supportive care technologies may have played an important role.…”
Section: T a B L E 2 (Continued)contrasting
confidence: 51%
See 4 more Smart Citations
“…2,15,25 Our team found the 10-year cumulative incidence of NRM was 14% (95% CI, 11-18) in patients with hematologic malignancies who underwent haplo-SCT. 3 The low NRM at 10 years post-transplant in our studies may be due to median age of our patients was 30 (9-64) years, which was much younger than most of the previous large studies. Meanwhile, the optimization of transplant procedures and the improvement of supportive care technologies may have played an important role.…”
Section: T a B L E 2 (Continued)contrasting
confidence: 51%
“…There were many previous large retrospective studies showed that the 10‐year NRM of long‐term survivors was 6%–12% in the cohort with a median age of 25–36 years 9,16,53 and 13%–35% in the cohort with a median age of 53–56 years 2,15,25 . Our team found the 10‐year cumulative incidence of NRM was 14% (95% CI, 11–18) in patients with hematologic malignancies who underwent haplo‐SCT 3 . The low NRM at 10 years post‐transplant in our studies may be due to median age of our patients was 30 (9–64) years, which was much younger than most of the previous large studies.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations